A swiftly tilting planet - L'Engle, Madeleine (New York Square Fish, 1978)
The youngest of the Murry children must travel through time and space in a battle against an evil dictator who would destroy the entire universe.
Keywords: Murry family (Fictitious characters) -- Juvenile fiction; Siblings -- Juvenile fiction; Time travel -- Juvenile fiction; Nuclear warfare -- Juvenile fiction; Space and time -- Juvenile fiction; Good and evil -- Juvenile fiction; Gifted teenagers -- Juvenile fiction; Young adult fiction, American -- Twentieth century